Implementation of a Sweet Potato Washing Machine for Brayan Grubi SMEs in Salaman District, Magelang Regency - Rany Puspita Dewi; Trisma Jaya Saputra; Sigit Iswahyudi; Adityo Noor Setyo Hadi Dharmo; Herru Santosa Budiono; Bagus Yustia; Cahyo Sejati (Universitas Muhammadiyah Surakarta, 2026)
Brayan Grubi, a small and medium enterprise (SME), located in Jetis, Menoreh Village, Salaman, Magelang Regency. It processes approximately 150 kg of sweet potatoes daily to make traditional food grubi. The grubi production process, from washing to packaging, is still done manually, known as